Anima rising : a novel - Moore, Christopher, 1957- (William Morrow, an imprint of HarperCollins Publishers, 2025)
"From New York Times bestselling author Christopher Moore comes a hilariously deranged tale of a mad scientist, a famous painter, and an undead woman's electrifying journey of self-discovery. Vienna, 1911. Gustav Klimt, the most famous painter in the Austrian Empire, the darling of Viennese society, spots a woman's nude body in the Danube canal. He knows he should summon a policeman, but he can't resist stopping to make a sketch first. And as he draws, the woman coughs. She's alive! Back at his studio, Klimt and his model-turned-muse Wally tend to the formerly-drowned girl. She's nearly feral and doesn't remember who she is, or how she came to be floating in the canal. Klimt names her Judith, after one of his most famous paintings, and resolves to help her find her memory. With a little help from Sigmund Freud and Carl Jung, Judith recalls being stranded in the arctic one hundred years ago, locked in a crate by a man named Victor Frankenstein, and visiting the Underworld. So how did she get here? And why are so many people chasing her, including Geoff, the giant croissant-eating devil dog of the North? Poor Things meets Bride of Frankenstein in Anima Rising, Christopher Moore's most ingenious (and probably most hilarious) novel yet"--